2020
DOI: 10.1167/jov.20.10.6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of visual short-term memory load and attentional demand on the contrast response function

Abstract: Visual short-term memory (VSTM) load leads to impaired perception during maintenance. Here, we fitted the contrast response function to psychometric orientation discrimination data while also varying attention demand during maintenance to investigate: (1) whether VSTM load effects on perception are mediated by a modulation of the contrast threshold, consistent with contrast gain accounts, or by the function asymptote (1 lapse rate), consistent with response gain accounts; and (2) whether the VSTM load effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 73 publications
(103 reference statements)
0
11
0
Order By: Relevance
“…Previous research has focused on how visual attention and working memory (WM) interact in the context of distractor interference ( Cashdollar et al, 2013 ; Downing, 2000 ; Konstantinou & Lavie, 2020 ; Lavie, 2010 ; Olivers et al, 2006 ). When shopping in the supermarket for a particular product, you must retrieve information from long-term memory about the appearance of the target and hold it in your WM, creating a target template (e.g., Bundesen, 1990 ; Duncan & Humphreys, 1989 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has focused on how visual attention and working memory (WM) interact in the context of distractor interference ( Cashdollar et al, 2013 ; Downing, 2000 ; Konstantinou & Lavie, 2020 ; Lavie, 2010 ; Olivers et al, 2006 ). When shopping in the supermarket for a particular product, you must retrieve information from long-term memory about the appearance of the target and hold it in your WM, creating a target template (e.g., Bundesen, 1990 ; Duncan & Humphreys, 1989 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a further behavioral study, detection sensitivity for a small peripheral shape during a letter visual search task was significantly impaired by VWM load, while cognitive load enhanced detection sensitivity (Konstantinou & Lavie, 2013). Konstantinou and Lavie (2020) further showed that a high VWM load increased the perceptual contrast threshold, which is mediated by neural responses in the early visual cortex of V1. These findings from visual awareness consistently support that VWM load reduces conscious visual perception, suggesting that it functions as a type of perceptual load rather than cognitive load.…”
mentioning
confidence: 89%
“…Because the flanker task is an indirect measurement of visual perception, those studies did not provide direct evidence of the effect of VWM load on visual perception. Konstantinou and colleagues directly probed the visual awareness of the target outside the focus of attention, exploring whether VWM load affected visual detection sensitivity (Konstantinou et al, 2012; Konstantinou & Lavie, 2013, 2020). They found neural and behavioral evidence that a high-color VWM load led to reduced detection sensitivity to incoming visual stimuli.…”
mentioning
confidence: 99%
“…Previous research has focused on how visual attention and working memory (WM) interact with each other in the context of distractor interference (Cashdollar et al, 2013;Downing, 2000;Konstantinou & Lavie, 2020;Lavie, 2010;Olivers et al, 2006). When shopping in the supermarket for a particular product you must retrieve information from long-term memory about the appearance of the target and hold this in your working memory, creating a target template (e.g., Bundesen, 1990;Duncan & Humphreys, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The load theory of attention and cognitive control, provides one concrete theoretical framework that captures the links between visual attention and WM (Forster et al, 2014;Konstantinou & Lavie, 2020;Lavie, 2005Lavie, , 2010Lavie et al, 2004). Load theory proposes that an increase in the perceptual difficulty of a primary task (perceptual load) serves to reduce the perceptual processing resources available to process task irrelevant distractors thereby reducing the extent to which these distractors interfere (Konstantinou & Lavie, 2020;Lavie et al, 2004). In addition, disrupting the availability of WM resources to maintain our goals, serves to increase interference from task irrelevant distractors (Cashdollar et al, 2013;Forster et al, 2014;Lavie, 2010;Lavie et al, 2004).…”
Section: Introductionmentioning
confidence: 99%